Integrating augmented reality virtual patients into healthcare training: A scoping review of learning design and technical requirements - Farshid Chahartangi; Nahid Zarifsanaiey; Manoosh Mehrabi; Bahareh Zeynalzadeh Ghoochani (PLoS ONE, 2025)
Augmented reality (AR) enables users to view the real world with enhanced digital information, making it a transformative tool in education. Virtual patients (VPs) technology is also defined as “a specific type of computer-based application that simulates real-world clinical scenario. AR and VPs offer interactive and immersive learning experiences, with AR enhancing the understanding of complex concepts and VPs providing hands-on practice in clinical scenario. This scoping review aims to identify an integrated learning design framework and the technical requirements for augmented reality-based virtual patient Simulation in healthcare professions education. This study employed a scoping review methodology that adhered to the PRISMA-ScR checklist and the Joanna Briggs Institute (JBI) guidelines, conducted between September and October 2024. The review covered six reputable databases: MEDLINE (PubMed), Science Direct (Elsevier), Web of Science (Clarivate), Cochrane library, ERIC, Scopus. A comprehensive search yielded 924 potential studies. Articles were selected via a two-stage screening process, involving title/abstract and full-text reviews based on predefined inclusion criteria. Disagreements were resolved through consultation, resulting in 27 studies being included. Eligible studies focused on augmented reality (AR)-based virtual patient (VP) technology in healthcare education, encompassing observational, quasi-experimental, and descriptive designs. Exclusions comprised grey literature, irrelevant studies, non-full-text articles, and non-AR/VP-focused research (e.g., standalone virtual reality). Various design approaches were employed, including situated learning, experiential learning, and the ADDEI model. The technical foundations of these studies were diverse, with Unity, UTTIME and PalpSim being commonly used software platforms. It is recommended that future studies thoroughly investigate each of these design framework and the technical requirements of VPAR, examining them in greater detail from various cultural, economic, social, and emotional perspectives. Tackling these problems will be a crucial stride towards enhancing and optimizing education for healthcare professions education.